Porous Electrospun Carbon Nanofibers Bearing TiO2 Hollow Nanospheres for Supercapacitor Electrodes - Suchunya Wongprasod; Nantawat Tanapongpisit; Peerawat Laohana; Thi My Huyen Nguyen; Hoang Quy Van; Sangmo Kim; Saranisorn Srikam; Somchai Sonsupap; Narong Chanlek; Mati Horprathum; Atchara Khamkongkaeo; Santi Maensiri; et al. (My University, 2024)
A facile fabrication method was introduced to enhance the specific surface area and porosity of the carbon nanofibers. The carbon nanofibers bearing TiO2 hollow nanosphere electrodes were synthesized using an electrospinning technique followed by heat treatment. Varying amounts of as-prepared TiO2 hollow nanospheres were incorporated into the polymer precursor to examine their impact on the electrode enhancement. The electrochemical performance of supercapacitor electrodes composed of carbon nanofibers bearing TiO2 hollow nanospheres was investigated. Results revealed that the specific capacitance of the bare carbon nanofibers electrode (170 F g–1 at a current density of 0.5 A g–1) was significantly improved upon when embedded with 5 wt % TiO2 hollow nanospheres of 191 F g–1. Additionally, the carbon nanofibers bearing 5 wt % TiO2 hollow nanosphere electrodes demonstrated excellent cycling stability, retaining 97% of its initial specific capacitance even after 10000 cycles. Additionally, the electrochemical performance of asymmetric supercapacitors from these electrodes was also demonstrated. These findings highlight the ability of as-prepared TiO2 hollow nanospheres to improve the efficiency of the carbon nanofibers electrode due to the optimum porosity to the amount of TiO2 hollow nanospheres in the carbon nanofibers, opening up possibilities for the development of high-performance supercapacitors.
Keywords: Electrospinning; Carbon fibers; Supercapacitor Materials and Fabrication